Demonstration of Low Work Function Perovskite SrVO3 Using Thermionic Electron Emission. (5th August 2022) - Lin, Lin; Jacobs, Ryan; Chen, Dongzheng; Vlahos, Vasilios; Lu‐Steffes, Otto; Alonso, Jose A.; Morgan, Dane; Booske, John
Abstract: Engineering a material's work function is of central importance for many technologies and in particular electron emitters used in high‐power vacuum electronics and thermionic energy converters. A low work function surface is typically achieved through unstable surface functional species, especially in high power thermionic electron emitter applications. Discovering and engineering new materials with intrinsic, stable low work functions obtainable without volatile surface species would mark a definitive advancement in the design of electron emitters. This work reports evidence for the existence of a low work function surface on a bulk, monolithic, electrically conductive perovskite oxide: SrVO3 . After considering the patch field effect on the heterogeneous emitting surface of the bulk polycrystalline samples, this study suggests the presence of low work function (≈2 eV) emissive grains on SrVO3 surface. Emission current densities of 10–100 mA cm –2 at ≈1000 °C, comparable to commercial LaB6 thermionic cathodes, indicative of an overall effective thermionic work function of 2.3–2.7 eV are obtained. This study demonstrates that perovskites like SrVO3 may have intrinsically low work functions comparable to commercialized W‐based dispenser cathodes and suggests that, with further engineering, perovskites may represent a new class of low work function electron emitters. Abstract : This work reports evidence for the existence of a low work function surface on a bulk, monolithic, electrically conductive perovskite oxide: SrVO3 . It shows an emission current density of 10–100 mA cm –2 at ≈1000 °C, with consideration and proper treatment of surface chemistry and patch field effect, indicating a promising 2.3–2.7 eV effective work function for potential thermionic emission applications.